DEVELOPMENT OF "CAPTAIN LUNGS 3D" AS A LEARNING MEDIA IN RESPIRATORY SYSTEM TOPIC TO ENHANCE STUDENTS CRITICAL THINKING SKILLS - Rahmi Vina Shafira, - (2020)
The Development Science and Technology in the 21st century requires four skills, one of them is the ability to think critically. Based on Facione, critical thinking skills are divided into six indicators, such as evaluation, interpretation, analysis, inference, explanation, and self-regulation. This research aims to develop and implement the "Captain Lungs 3D" application as a learning media on respiratory system topics to enhance students' critical thinking skills. This research used Research and Development method, and there is pre-test and post-test also. Sampling used in this research was convenience sampling, which participated in 60 students of 9th-grade students public school in Bandung. Game-based learning is also used in delivering material during teaching learning process. The objective test used as a research instrument for pre-test and post-test design. Test items that are used is based on the Facione indicator of Critical Thinking Skills. Based on the analysis result, the Normalized gain is 0.48. From the result that used the Wilcoxon Signed Rank Test, the hypothesis in this research is accepted. The value of Asymp (2-tailed) is 0.000, with the level of significant value is 0.05. At the end of class, students are asked to giving feedback based on the questionnaire that is already given about game-based learning implemented on "Captain Lungs 3D". The research shows that there is a significant difference in "Development of "Captain Lungs 3D" as a Learning Media in Respiratory System Topic To Enhance Students Critical Thinking Skills.